Relationship between strategies and maxims combination pattern with Malay politeness in radio talk show - Johari, Arina; Mokhtar, Nor Zainiyah Norita; Mohd Ismath, Nurul Hanilah; Ismail, Mohamad Zuber (European Union Digital Library, 2019)
This study was conducted in order to explore and identify the use of Strategies and Maxims Combination Pattern (SMCP) by participant of talk show titled “Celik Mata, Reset Minda Orang Yang Tenang” aired by IKIMfm radio and its relation with The Features of Malay Politeness (FMP). The analysis focuses on the host (P), invited guest (TU) and callers (PG) and facebook respondent (FBR) dialogues in the content structure of talk show. Some methods are applied such as text analysis, transcription, encoding and others. The four patterns of combined strategies that contain P1, P2 and P3 as the core patterns and optional patterns have been formed, namely Pattern A, Pattern B, Pattern C and Pattern D. P1 represents the Off Record sans match which was seen as optional, whereas P2 (a Politeness strategy, both positive and negative) was observed to be used as a core pattern. P3 (Off Record strategy) is used as an option in phrases that involved a certain combination that can be deemed as a core pattern. The findings show that all the participants have applied Pattern A second variation to achieve conflict-free situations. It’s also shows a significant relation with the variation of features in FMP, namely RPSS+TF+RI and incomplete FMP - involving two FMPs and one FMP.